2016
DOI: 10.5851/kosfa.2016.36.6.760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Processed Sulfur on the Meat Quality in Pork under Aging

Abstract: The present study was performed to determine the effect of dietary supplementation with processed sulfur on the quality and stability of vacuum packaged pork during aging time. All groups were designated into two groups; NP, a group fed basal diet and SP, a group fed basal diet and processed sulfur, 3 g/kg feed. Following vacuum packaging, Longissimus dorsi muscles were vacuum-packaged and stored under refrigerated condition (1-2°C) for 21 d. Weight loss of the SP group was lower (p<0.05) than that of the NP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Increased lightness of wet-aged pork loins can be explained by the fact that the high moisture content contributed to increasing the reflectance spectra of wet-aged pork loins (Bertram et al, 2004). Similarly, Hwa et al (2016) observed that the aging time under vacuum packaging resulted in an increase in lightness. In addition, the redness of dry-aged pork loins was lower (p \ 0.001) than that of wet-aged pork loins, and the reduction in redness occurred in both dry-aged and wet-aged pork loins from 7 to 14 days (p \ 0.001).…”
Section: Metmyoglobin Measurementmentioning
confidence: 92%
“…Increased lightness of wet-aged pork loins can be explained by the fact that the high moisture content contributed to increasing the reflectance spectra of wet-aged pork loins (Bertram et al, 2004). Similarly, Hwa et al (2016) observed that the aging time under vacuum packaging resulted in an increase in lightness. In addition, the redness of dry-aged pork loins was lower (p \ 0.001) than that of wet-aged pork loins, and the reduction in redness occurred in both dry-aged and wet-aged pork loins from 7 to 14 days (p \ 0.001).…”
Section: Metmyoglobin Measurementmentioning
confidence: 92%